Optimisation of Centrifuge Operating Conditions for Dewatering Physically Conditioned Faecal Sludge from Urban - Semiyaga, Swaib; Niwagaba, Charles B.; Nyenje, Philip M.; Kansiime, Frank (Environmental Technology & Innovation, 2017)
Decentralised faecal sludge (FS) dewatering in urban slums using centrifugation technology has potential to reduce public health risks and environmental pollution caused by indiscriminate disposal of untreated FS. A laboratory-scale centrifuge was applied to dewater FS from lined pit latrines, conditioned with sawdust and charcoal dust. Response surface methodology and central composite design were used to construct and model relationships between independent variables (FS volume, centrifugation time and speed) and the dependent variable (per cent cake solids) for unconditioned and conditioned (sawdust and charcoal dust) FS. The results demonstrated that the centrifugation technology can yield more per cent cake solids at reduced speeds when physically conditioned. Rotational speed was a significant parameter for unconditioned (original) () and charcoal dust conditioned FS (). Significant parameters for sawdust conditioned FS were speed () and quadratic effect of time (). An optimal centrifugation time of 20 minutes and centrifugation container volume of 50 mL at 70–80% full of FS for conditioned FS were obtained. The centrifugation speeds tested in this paper provide critical information for proto-type design of a hand-powered centrifuge, the operating conditions and its subsequent set-up. This can serve as an option for dewatering FS from commonly used sanitation facilities in urban slums, thereby enabling decentralised treatment to reduce costs of FS management and support resource recovery at the source.
Keywords: Cake solids; Centrifugation speed; Centrifugation time; Faecal sludge; Response surface ,methodology.